2011
DOI: 10.1016/j.ymeth.2011.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of multifunctional phi29 pRNA nanoparticles for specific delivery of siRNA and other therapeutics to targeted cells

Abstract: Recent advances in RNA nanotechnology have led to the emergence of a new field and brought vitality to the area of therapeutics (Guo P, The Emerging Field of RNA Nanotechnology, Nature Nanotechnology, 2010). Due to the complementary nature of the four nucleotides and its special catalytic activity, RNA can be manipulated with simplicity characteristic of DNA, while possessing versatile structure and diverse function similar to proteins. Loops and tertiary architecture serve as mounting dovetails or wedges to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 103 publications
1
65
0
Order By: Relevance
“…Toolkit I: Hand-in-hand toolkit for assemblage of pRNA nanoparticles by extending interlocking loops Previously, we have reported that the interlocking loops of phi29 pRNA can be used for constructing RNA dimers, trimers, and hexamers through hand-in-hand interactions (Guo et al 1998Chen et al 1999;Shu et al 2003Shu et al , 2011cKhaled et al 2005). However, the resulting particles were not found to be thermodynamically stable enough for nanotechnological applications.…”
Section: Resultsmentioning
confidence: 99%
“…Toolkit I: Hand-in-hand toolkit for assemblage of pRNA nanoparticles by extending interlocking loops Previously, we have reported that the interlocking loops of phi29 pRNA can be used for constructing RNA dimers, trimers, and hexamers through hand-in-hand interactions (Guo et al 1998Chen et al 1999;Shu et al 2003Shu et al , 2011cKhaled et al 2005). However, the resulting particles were not found to be thermodynamically stable enough for nanotechnological applications.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, computationally designed [72] and experimentally tested [32,35,73,74] nanorings take advantage of the so-called RNA kissing loop ineracting motifs (Figure 1, case 4). Other examples use the structural motifs extracted from the phage phi29 pRNAs [75] that were widely used in the engineering of multiple stable and functional RNA nanoscaffolds [76][77][78][79][80][81][82][83][84][85][86][87]. An alternative to the tecto-RNA designing strategy is exemplified by the nanocubes (Figure 2) [88,89].…”
Section: Multifunctional Rna and Dna Nanoparticlesmentioning
confidence: 99%
“…The second class encompasses tectonic units that can be split into structural motifs and interacting motifs possessing discrete secondary and tertiary structures which can be combined to rationally produce self-assembling nanoparticles with predictable, multi-dimensional structures in vivo or in vitro. Some examples of structural motifs are double-stranded RNA helices, C-loops [72] (which increase the helical twists), kink-turns [97], right angle motifs [78], tRNA motifs [98] (the latter three bends within an oligonucleotide strand); as well as three [76,99], four [100,101], and five way junctions [100]. Examples of interacting motifs are tetraloopreceptors [74] (an interaction between a four-base hairpin "tetra-loop" motif and a "receptor" structured internal loop motif), kissing loops [102,103] (coaxial stacking motifs), sticky ends [104,105], and paranemic motifs [81] (an interaction of "crosshatched" stacking helices).…”
Section: Rna Architectonic Approach (Tectorna)mentioning
confidence: 99%
“…It has greatly enhanced simplicity and biocompatibility when compared with peptide, liposomal, or synthetic nanomaterial conjugation for RNA-based functionalities; RNA nanoparticles can be equipped with custom tailored combinations of therapeutic agents or biosensors, which show promise to improve targeting and penetration of cells or tissues safely and efficiently [76,95,107], provide "cocktail"-like multi-target therapies [106], advanced imaging or imaging concurrent with therapeutics [110]. In addition, they can do so while guaranteeing strict control of the 3D orientation and stoichiometry of those agents [102,104].…”
Section: Rna Architectonic Approach (Tectorna)mentioning
confidence: 99%
See 1 more Smart Citation